2016
DOI: 10.1186/s12958-016-0193-6
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of preimplantation genetic screening (PGS) is compromised by degree of mosaicism of human embryos

Abstract: BackgroundTo preclude transfer of aneuploid embryos, current preimplantation genetic screening (PGS) usually involves one trophectoderm biopsy at blastocyst stage, assumed to represent embryo ploidy. Whether one such biopsy can correctly assess embryo ploidy has recently, however, been questioned.MethodsThis descriptive study investigated accuracy of PGS in two ways. Part I: Two infertile couples donated 11 embryos, previously diagnosed as aneuploid and, therefore, destined to be discarded. They were dissected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
72
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(76 citation statements)
references
References 20 publications
2
72
0
1
Order By: Relevance
“…Overall, 8/22 biopsies (36.6 %) revealed either mosaicism or inconclusive results. Also supporting above described mouse study, two independent groups reported surprisingly high live birth rates of healthy, genetically normal infants after transfer of embryos after PGS 2.0 reported to be aneuploid (mosaic) [15,16]. These results are indicative of significant false-positive rates following PGS 2.0 and raise serious concerns about the potential discarding of perfectly normal embryos in large quantities in current PGS 2.0 utilization.…”
Section: The Biology Of Mosaicismsupporting
confidence: 64%
“…Overall, 8/22 biopsies (36.6 %) revealed either mosaicism or inconclusive results. Also supporting above described mouse study, two independent groups reported surprisingly high live birth rates of healthy, genetically normal infants after transfer of embryos after PGS 2.0 reported to be aneuploid (mosaic) [15,16]. These results are indicative of significant false-positive rates following PGS 2.0 and raise serious concerns about the potential discarding of perfectly normal embryos in large quantities in current PGS 2.0 utilization.…”
Section: The Biology Of Mosaicismsupporting
confidence: 64%
“…In the group of women older than 40 years studies with PGS on trophoblast cells have shown that a large number of embryos produced are chromosomally abnormal, thus explaining at least in part why there is such high BEmbryo Wastage^in this age group [16,34]. However, it remains to be seen whether this technique will ultimately lead to a significant improvement in live birth rate since it is still error-prone with the risk of discarding embryos wrongly diagnosed as aneuploidy because of mosaicism [21][22][23]. Other barriers such as the cost, including the possible need to cryopreserve embryos and defer transfer, and invasiveness of the biopsy and any potential long term effects also need to be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Recent improvements in pre-implantation genetic screening (PGS) techniques for identifying normal euploid embryos have been associated with higher pregnancy and delivery rates when analyzed per transfer [15][16][17]; however, several barriers to its widespread use still exist, including cost and particularly the lack of unequivocal evidence that its use improves pregnancy and live birth rates, particularly for patients with few embryos available for testing, due to the presence of high rates of mosaicism in the trophoblast cells [18][19][20][21][22][23]. Other studies have reported on the use of proteomics and metabolomics to identify factors in embryo culture media that may be predictive of embryo competence or assessing gene expression in cumulus cells; however, even these methods are still inefficient and not ready yet for clinical application [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Tortoriello et al performed a second trophectoderm biopsy in embryos initially deemed by cytogenetics to be aneuploid and found that 9/27 (33 %) were euploid when using a different technology and a different genetic laboratory [18]. Gleicher et al found a similar false positive rate (36.4 %) when re-testing dissected embryos initially reported as aneuploid [19]. To date, studies have reported similar miscarriage rates in patients undergoing in vitro fertilization when compared to a sub-fertile population; thus, even if some laboratory conditions are correlated with increases in postfertilization mosaicism, that does not automatically correlate to an increase in miscarriages [20].…”
mentioning
confidence: 99%